Disaster Education in The Perspective of The Qur'an - Mukhtarom, Asrori (Nadwa: Jurnal Pendidikan Islam, 2023)
Disasters are events that have an impact on death, material loss, and deep psychological trauma for disaster victims. To minimize the impact of major disasters, disaster education is needed for the community, especially those living in areas prone to earthquakes, volcanic eruptions, floods and landslides. This research seeks to find the concept of disaster education from the perspective of the Qur'an. The method used in this research is qualitative with literature review, and the method used is maudhu'i interpretation or thematic interpretation. The results of this study indicate that disaster education from the Al-Qur'an perspective is an effort to provide knowledge about disaster issues based on the Al-Qur'an. Disaster Education from Al-Qur'an Perspective is carried out by introducing the community to disasters and their types, such as earthquakes in QS. Al-A'raf [7]: 78, the volcano erupts in QS. An-Naml [27]: 88, tsunami in QS. Al-Infitar [82]: 3, flood in QS. Al-Ankabut [29]: 14, drought in QS. Yusuf [12]: 48, and infectious disease outbreaks in QS. Al-Anfal [8]: 133. Furthermore, providing disaster prevention education by inviting the public to protect the environment from damage in QS. Al-A'raf [7]: 56. So try to save yourself from a life-threatening disaster in QS. Al-Baqarah [2]: 195. Pray when disaster strikes in QS. Ar-Rum [30]: 33, don't give up in facing disasters, and remain optimistic about life after disasters in QS. Az-Zumar [39]: 53. Furthermore, providing assistance to disaster victims both material and immaterial (prayers) in QS. Al-Maidah [5]: 2. Disaster education in the Qur'an uses informative and solutive language. Keywords: Education, Disaster, and the Qur'an